Project-Based Learning Approach and Entrepreneurial Skills of Grade 9 TLE Cookery Students - Pastorpide, Daisybel L. (Future Science / FSH-PH Publications, 2025)
This study examined the effectiveness of project-based learning (PBL) in enhancing the entrepreneurial skills of Grade 9 TLE cookery students at Amontay National High School for SY 2024–2025. It aimed to assess pre- and post-test scores in entrepreneurial competencies, compare the effectiveness of haptic engagement and cooperative & team-based learning, and determine the significance of score differences. A quasi-experimental design with pre- and post-tests was used. Purposive sampling selected 80 students, split between haptic engagement and cooperative learning groups. A validated researcher-made assessment measured skills in business planning, marketing, financial literacy, leadership, creativity, problem-solving, and communication. Findings showed significant improvement in entrepreneurial competencies after PBL. Both strategies enhanced skills, though cooperative learning showed higher post-test gains in most areas. T-test results confirmed statistically significant differences before and after PBL, affirming its effectiveness. The results suggest that structured PBL strengthens student competencies by offering real-world learning experiences. The study recommends that teachers and school heads integrate structured PBL approaches into entrepreneurship instruction, supported by experiential learning and partnerships with industry. Curriculum developers are encouraged to embed PBL in TLE subjects to promote innovation and collaboration. Future research may explore its long-term impact, including employer perspectives and digital entrepreneurship integration. This study affirms PBL as a valuable tool for developing essential entrepreneurial skills and preparing students for active economic participation.